ANALISIS PENGARUH CAR, NPL, LDR DAN NIM TERHADAP PROFITABILITAS PERBANKAN (Studi Kasus Pada Bank Umum Yang Tercatat Pada BEI Tahun 2008-2012) - Pramitha Kusuma Dewi; M. Mulyadi; A. Abdurrakhman (JAFFA, 2015)
This study aims to examine the effect of the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), and the loan to deposit ratio (LDR) of the Return on Assets (ROA) as a proxy of profitability of the Banking Companies Listed on the Stock Exchange from 2008 to 2012. the data used in this study were obtained from the Annual Financial Statements of Banking Companies Listed on the Stock Exchange from 2008 through 2012 published by Bank Indonesia. After passing through the stage purposive sample, then the sample is worth using as many as 20 of Banking Companies Listed on the Stock Exchange. During the observation period of the study showed that the data were normally distributed. Under the normality test, multicollinearity, heteroscedasticity test and autocorrelation test found no variables that deviate from the classical assumptions.This shows the available data has been qualified using multiple linear regression model. The results showed that the variables NPL (Non Performing Loans) and NIM (Net Interest Margin) influence on ROA (Return on Assets), while for the variable CAR (Capital Adequacy Ratio) and LDR (Loan to Deposit Ratio) has no effect on ROA (return on Assets).